Effect of tea catechins on gut microbiota in high fat diet‐induced obese mice. (11th February 2023) - Liu, Jianhui; Ding, Huafang; Yan, Chi; He, Zouyan; Zhu, Hanyue; Ma, Ka Ying
Abstract: BACKGROUND: Tea catechins have been shown to have beneficial effects on the alleviation of obesity, the prevention of diabetes, and the amelioration of metabolic syndrome. The purpose of the present work is to explore the underlying mechanisms linking the intestinal microbiota and anti‐obesity benefits of green tea, oolong tea, and black tea catechins in C57BL/6J mice fed with a high‐fat diet (HFD). RESULTS: The results indicated that, after the dietary intake of three tea catechins, obesity and low‐grade inflammation were significantly alleviated. Hepatic steatosis was prevented, and this was accompanied by the upregulation of the mRNA and protein expressions of hepatic peroxisome proliferator‐activated receptor α (PPAR α ). Metagenomic analysis of fecal samples suggested that the three tea catechins similarly changed the microbiota in terms of overall structure, composition, and protein functions by regulating the metabolites, facilitating the generation of short‐chain fatty acids (SCFAs), and repressing lipopolysaccharides. CONCLUSION: The anti‐obese properties of three tea catechins were partially mediated by their positive effect on gut microbiota, hepatic steatosis alleviation, and anti‐inflammatory activity. © 2023 Society of Chemical Industry.